1991
DOI: 10.1002/nur.4770140204
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of diurnal sleep patterns in infants of adolescent and adult single mothers

Abstract: Sleep behavior has been related to both child and environmental factors, but the relative importance of these factors is not yet clear. This study was an examination of the relation of diurnal sleep patterns to perinatal risk, infant temperament, home environment, parenting stress, emotional support, and social class. Twenty-three adolescent and 23 single adult mothers and infants were assessed in the home at 4 and 12 months. Percent sleep during the night was most strongly related to parenting stress and vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
(30 reference statements)
0
5
1
Order By: Relevance
“…This previous finding was present only among mothers on maternity leave (Sinai & Tikotzky, 2012), a potential moderator our study did not take into account. Furthermore, though the present study did not replicate previously found associations between maternal stress and infant sleep problems or night sleep behaviors, our sample was drawn from a low-risk population, in contrast to studies examining high-risk mothers (Becker et al, 1991; Sidor et al, 2013) or mothers on maternity leave compared to working mothers (Sinai & Tikotzky, 2012). …”
contrasting
confidence: 59%
See 1 more Smart Citation
“…This previous finding was present only among mothers on maternity leave (Sinai & Tikotzky, 2012), a potential moderator our study did not take into account. Furthermore, though the present study did not replicate previously found associations between maternal stress and infant sleep problems or night sleep behaviors, our sample was drawn from a low-risk population, in contrast to studies examining high-risk mothers (Becker et al, 1991; Sidor et al, 2013) or mothers on maternity leave compared to working mothers (Sinai & Tikotzky, 2012). …”
contrasting
confidence: 59%
“…Increased maternal stress at 4 months has been associated with concurrent infant sleep problems (Sidor, Fischer, Eickhorst, & Cierpka, 2013) and a decrease in the percentage of night sleep (Becker, Chang, Kameshima, & Bloch, 1991), as well as with greater variability in infants’ night sleep at 12 months, with infant temperament serving as a possible mediator in this latter relation (Becker et al, 1991). Furthermore, greater maternal stress has been associated with infants’ sleep problems and, among mothers on maternity leave, with longer night wakefulness and shorter day sleep duration (Sinai & Tikotzky, 2012).…”
mentioning
confidence: 99%
“…However, research has revealed that becoming a mother can be a stressful experience and more complex than previously thought. Many factors are related to the development of parenting stress including social support (Gage & Christensen, 1991;Levy-Shiff et al, 1998); self-efficacy (Lutenbacher, 2002;Reece & Harkless, 1998); personality (Belsky, Crnic, & Woodworth, 1995;Mulsow et al, 2002;Younger, 1991); cognitive appraisal and every day stressors (Levy-Shiff et al, 1998;Tessier et al, 1992), and infant temperament, difficulty, birth weight and sleep patterns (Becker, Chang, Kameshima, & Bloch, 1991;Gelfand et al, 1992;Halpern, Brand, & Malone, 2001;Pridham, Chang, & Chiu, 1994;Secco & Moffatt, 2003;Terry, 1991). The mother's perception of stress and the degree of role ambiguity in the mothering role also may affect the mother's transition to parenthood (Gage & Christensen, 1991;Reece & Harkless, 1998).…”
Section: Review Of Literaturementioning
confidence: 97%
“…C-section infants have been found to have more wakefulness during the nighttime at 3 and 5 months in comparison to vaginally delivered infants (Alley & Rogers, 1986). An infant who, while in the crib, is awake just as much at night as during the day may be a source of frustration for a new mother (Becker, Chang, Kameshima, & Bloch, 1991), especially if she is recovering from a surgical delivery. Accordingly, mother -infant interactional differences may contribute to persistance of the early effects of the surgical birth process.…”
Section: Figurementioning
confidence: 99%